Using infographics to go public with SoTL - Keogh, Bryn; Nowell, Lorelli; Laios, Eleftheria; McKendrick-Calder, Lisa; Molitor, Whitney Lucas; Wilbur, Kerry (My University, 2024)
There has been a call to amplify the scholarship of teaching and learning (SoTL) and expand its reach by engaging with audiences outside the academy. In this paper, we share our journey in crossing disciplinary boundaries and creating a SoTL-informed infographic for public consumption. As the field of SoTL continues to evolve, infographics hold tremendous potential to communicate SoTL to various stakeholders, including educators, students, administrators, policymakers, and the public. We outline best practices in infographic development and the potential of infographics as a tool for taking SoTL public, emphasizing their visual appeal and effectiveness in conveying complex information. We conclude by discussing the implications of using infographics to advance SoTL communication. The efforts of our group serve as a valuable example of how infographics can be used to bring SoTL knowledge out of academia and into the public domain.
Keywords: SoTL; best practices; knowledge sharing; public engagement; infographics